2018
DOI: 10.3168/jds.2018-14832
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral changes in group-housed dairy calves infected with Mannheimia haemolytica

Abstract: Monitoring sickness behavior may improve identification, management, and welfare of sick animals. The objective of this study was to characterize components of sickness behavior in group-housed dairy calves, using an experimental disease challenge model with Mannheimia haemolytica (MH). Holstein bull calves (aged 3-7 weeks; 58.0 ± 12.0 kg of body weight) were group-housed based on age and body weight in sand-bedded pens (6 calves/pen, 6.6 m 2 /calf) and provided pasteurized waste milk (8 L/d) 2× /d and grain c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 36 publications
3
17
1
Order By: Relevance
“…Self-grooming is an important maintenance behavior and is subject to physiological and environmental factors. Sickness and disease have been shown to decrease self-grooming in calves (Borderas et al, 2008;Hixson et al, 2018), and certain bedding materials increase self-grooming (Panivivat et al, 2004). Previous studies have found that pre-weaned group-housed calves spend 35 min/11 h (Hepola et al, 2006) and individually housed calves spend 20 min/8 h observation period selfgrooming (Horvath and Miller-Cushon, 2017), which is greater than the amount of time we observed calves performing self-grooming (<18 min/12 h for both treatments).…”
Section: Behaviorcontrasting
confidence: 61%
“…Self-grooming is an important maintenance behavior and is subject to physiological and environmental factors. Sickness and disease have been shown to decrease self-grooming in calves (Borderas et al, 2008;Hixson et al, 2018), and certain bedding materials increase self-grooming (Panivivat et al, 2004). Previous studies have found that pre-weaned group-housed calves spend 35 min/11 h (Hepola et al, 2006) and individually housed calves spend 20 min/8 h observation period selfgrooming (Horvath and Miller-Cushon, 2017), which is greater than the amount of time we observed calves performing self-grooming (<18 min/12 h for both treatments).…”
Section: Behaviorcontrasting
confidence: 61%
“…Self-grooming has hygienic, thermoregulatory, sensory stimulation, and stress-relieving effects (Spruijt et al, 1992). Our data show an decreasing in body care(grooming) was agreed with previous finding of ( Fogsgaard et al, 2012;Toaff-Rosenstein et al,2016 andHixson et al,2018) this due to as part of an energyconservation strategy (Hart, 1988) also, Lethargy produced from cytokines released reduced grooming (Hart, 1988) While, differences between grooming between LSD and FMD may related to presence of skin conditions in LSD which increase oral grooming (Mooring et al, 1996) Moreover, data obtained in fig( ??? ) show decreasing in exploratory behavior in FMD infected animals (analgesic or not )was agreed with previous finding of ( Arakawa et al, 2010;Proudfoot et al, 2014 andHixson et al,2018) who stated infected animal reduced social interactions this may due to pathogen-associated molecular patterns, innate immune cells to release inflammatory cytokines (Vilcoek, 1998) called interleukin-1b (IL-1b) which link the nervous, immune, and endocrine systems to modulate sickness behaviors in accordance with external factors and internal physiological (Dantzer 2004); sickness behaviors can suppress social behavior (Michael et al, 2014) which leading to reduce social exploration (Kent et al, 1992) a reduction in the time spent investigating an unfamiliar conspecific is a commonly used measure of sickness behavior (Arakawa et al, 2009) and this social withdrawal may have an evolutionary function to decrease disease transmission (Loehle, 1995) , while, the non-significant difference in sickness behavior (exploration and body care) in LSD infected animals (analgesic or not ) was agreed with the finding of (Francisco and Donald, 2002) who stated that there were no differences in times receiving aggression.…”
Section: Sickness Behaviorsupporting
confidence: 93%
“…Monitoring sickness behavior may improve identification, management, and welfare of sick animals and behavioral changes may be useful indicators of early stages of disease. (Hixson et al, 2018). Sickness and pain can lead to some behavioral changes (Lomb et al,2017) as, diseased animals decreased its activity in exploration and body care as well as poor appetite which done as an adaptive response by it to enhance disease resistance and facilitate recovery from disease (Johnson, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…This behavior also responds to various physiological and environmental factors, suggesting a possible link with calf comfort and welfare. For example, a reduction in duration of self-grooming has been reported following experimental disease challenge models that induce sickness behavior (Borderas et al, 2008;Hixson et al, 2018). Additionally, bedding material affects time spent self-grooming, with calves performing more self-grooming when housed on sand and rice hulls compared with long wheat straw, possibly due to the bedding material sticking to their coat (Panivivat et al, 2004).…”
Section: Discussionmentioning
confidence: 99%